Pengembangan Media Pembelajaran Roulette Bingo Pada Pembelajaran Bahasa Indonesia Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas IV Sekolah Dasar - Muthia Khairani; Fitri Hilmiyati; Imas Mastoah; Hanafi Hanafi; Oman Farhurohman (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to develop and evaluate the effectiveness of Roulette Bingo as an innovative learning medium to enhance critical thinking skills in fourth-grade Indonesian language learning. The research employed a mixed-methods approach within a Research and Development (R&D) framework using the ADDIE model, involving stages of analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, questionnaires, tests, and documentation, and analyzed using descriptive statistics and N-Gain analysis. The validation results indicated that the developed media achieved a very high feasibility level, supported by expert judgments in media, material, and language aspects. Implementation findings demonstrated a significant improvement in students’ critical thinking skills, as reflected in the increase from pre-test to post-test scores and a high N-Gain category. Qualitative findings also revealed increased student engagement, collaboration, and active participation during learning activities. These results confirm that Roulette Bingo serves as an effective, interactive, and practical instructional medium aligned with contemporary pedagogical demands. The study highlights the importance of integrating game-based learning to foster higher-order thinking skills in elementary education.